Antibody and immune memory persistence post infant hepatitis B vaccination - Shuaibu, Hudu Abdullahi; A. Malik, Yasmin; Mohd Taib, Niazlin; Mohammed Harmal, Nabil Saad; Adnan, Ariza; Alshrari, Ahmed Subeh D.; Sekawi, Zamberi (Dove Medical Press, 2013)
OBJECTIVES: This study aimed to evaluate the level of hepatitis B immunity among undergraduate students 23 years after commencement of the nationwide hepatitis B childhood immunization program in Malaysia. METHODS: A total of 402 serum samples obtained from volunteer undergraduate students were screened for the presence of hepatitis B surface antibodies using qualitative ELISA. RESULTS: Results showed that 62.7% of volunteers had protective anti-hepatitis B surface antigens (≥10 IU/L), of whom 67.9% received three doses of the vaccine. The estimated post-vaccination immunity was found to be at least 20 years, indicating persistent immunity against hepatitis B and a significant association (P < 0.05) with duration of vaccination. Anamnestic response 1 month post-hepatitis B booster was 94.0% and highly significant (P < 0.01). Isolated antihepatitis B core antigen (anti-HBc) prevalence was found to be 5.0%, all having had a positive anamnestic response. CONCLUSION: Immunity after primary vaccination with hepatitis B recombinant vaccine persists for at least 20 years post-vaccination, with significant association with the number of vaccinations. Furthermore, the presence of anamnestic response to booster vaccine indicates long-lasting immunity despite decreasing antibody levels; therefore, the need for hepatitis B vaccine boosters may not be of significant benefit after complete infant vaccination.